THE RELATIONSHIP BETWEEN ECONOMIC PRESSURE, HUSBAND-WIFE INTERACTION, AND HUSBAND’S MARITAL SATISFACTION - I`lma Fadillah Nur Anisa Gunawan; Diah Krisnatuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Marital satisfaction affects many aspects of people’s individual and social life. It is affected by factors such as economic strain and the couple’s interaction. Therefore, this study was conducted to determine the relationship between economic pressure, husband-wife interaction, and husband's marital satisfaction. The data for this study were gathered from an online survey of 33 informal working husbands and 32 formal working husbands from West Java. The respondents were selected by using the purposive sampling technique. The Economic Pressure Questionnaire and Interpersonal Behavior Scale measured economic pressure and husband-wife interaction. ENRICH Marital Satisfaction instrument has been used to measure a husband's marital satisfaction. The findings revealed that economic pressure and husband-wife interaction significantly relate to the husband’s marital satisfaction. Multiple regression analysis was used to analyze the relative strength of independent variables in predicting a husband’s marital satisfaction. The results indicated that husband-wife interaction was found to have the strongest influence on a husband’s marital satisfaction. Findings imply that there is a need for strategies to improve the quality of husband-wife interactions to help prevent divorce prepared by both partners and related parties.